Influence of Carica papaya L. consumption on the lymphocyte phenotypes in males and females - Jumat, Nur Ramziahrazanah (2015)
The immune system that protects human body from infection consists of innate and adaptive immunity. Cytotoxic immune response specifically provides protection against intracellular pathogens and tumor cells. Natural killer (NK) and cytotoxic CD8+T cells (CTLs) are cells of innate and adaptive immunity, respectively, that participates and play major roles in cytotoxic immune response. Immune-related conditions such as cancer and autoimmune diseases present with gender biasness and may be linked to sex hormones which modulates the immune system. Fruits and vegetables boost the immune response and may also have effect on the endocrine system. The impact of fruits and vegetables on the immune system of the different genders is still unknown. Carica papaya is one of the commonly consumed fruits in Malaysia but traditionally implied unsuitable for pregnant women. The current study was carried out to evaluate hormonal changes and alterations in lymphocytes phenotypes from consumption of ripe papaya. Eighteen healthy individuals, (n=9 and female, n=9) were recruited and underwent a four-day controlled diet study. Volunteers were abstained from taking papaya for two days and followed by two days of papaya exposure. Whole blood samples were collected on the third and fifth day of experiment. Lymphocyte subsets distribution, activation, IFN-γ production, cytokine receptors (IL-21R, IL-12Rβ2 and IL-15Rα) expression, CD107a degranulation and NK cell cytotoxicity were performed using flow cytometry. Levels of sex hormones (17β-estradiol, progesterone and testosterone) were also determined and correlated with the immune profiles. Papaya consumption significantly increased progesterone levels in all the volunteers (p=0.039, n=18) and levels of 17β-estradiol (p=0.036, n=9) and progesterone (p=0.039, n=9) in females. Increased percentage of CD4+T cells (p=0.028, n=18) but reduced percentage of CD3-CD56+IL-21R+ (p=0.031, n=18) following C. papaya consumption were generally observed in all volunteers. In females, the percentage of CD4+ T (p=0.036, n=9) and CD8+ T (p=0.038, n=9) cells were significantly increased and CD3-CD56+IL-21R+ (p=0.035, n=9) cells remained significantly suppressed after papaya consumption. However, these effects were not significant in males. C. papaya consumption increased the percentage of CD4+CD45RA-CD69- central/effector memory T cells (p=0.017, n=8) but reduced percentage of CD8+ T (p=0.028, n=9) and absolute count of B cells (p=0.021, n=9) in males. Increased percentages of NK cell cytotoxicity when co-cultured with K562 cells were observed for both ½ (p=0.032, n=18) and ¼ (p=0.022, n=18) diluted whole blood when compared in all volunteers after C. papaya consumption but not within gender. Correlation analysis showed 17β-estradiol levels in females (n=9) were positively correlated with absolute count of B, CD4+ T and CD3+ T cells and NK cells producing IFN-ɣ after papaya consumption but negatively associated with percentage of CD8+ T cells and CD4+CD25+ T cells. In addition, levels of progesterone in females (n=9) were also significantly associated with percentage of CD4+CD45RA+CD25+ of late activated effector T cells after C. papaya consumption. Testosterone levels in males (n=9) positively correlated with percentage of CD4+ T cells but negatively correlated with CD8+ T cells count after C. papaya consumption. Thus, papaya consumption modulated many immune profiles including cytotoxic responses as a response to changes in the hormone levels.